Dakwah Digital di Tiktok: Analisis Self-Regulatio dan Pesan Mindfulness dalam Mewjudkan Ketenagan Diri - Nur Hikmah; Qudratullah (ALAMTARA, 2025)
This study analyzes the communication strategies of Islamic preaching on TikTok in responding to the challenges of digital anxiety among the younger generation. The main focus of the study is the exploration of the casual (chill) style of preaching and self-regulation techniques as an effort to create calm in the audience. It uses qualitative methods with a content analysis design on 80 popular Islamic preaching videos (2023–2025) and in-depth interviews with 10 informants (aged 18–30). Theoretically, this study integrates Maslow's Hierarchy of Needs Theory, specifically the levels of safety and self-actualization needs as a framework for interpreting the effects of content. The results show that the chill style, through an empathetic approach and friendly visuals, combined with self-regulation instructions (reflective pauses and breathing techniques), is proven effective in reducing momentary anxiety scores and increasing audience relaxation. The success of this strategy is indicated by an increase in the audience's ability to manage negative emotions after consuming the content. The limitations of this study lie in the duration of the calming effect, which is temporary and highly dependent on user personalization algorithms. This study recommends the integration of health literacy